Experimental study of fat derived pellets promoting wound healing in rats - Li Zeng (Taylor & Francis Group, 2021)
To observe the effect of fat derived pellets (FDP) on wound healing in rats. Methods: the inguinal fat of rats was obtained, and the FDP were obtained after centrifugation. The cell activity and growth factor secretion of FDP were measured. The wounds in rats were created and FDP was used to treat the wound of rats. The phenotype of macrophages and the expression of angiogenic factors expression in wounds were measured. Results: the cell viability in FDP remains in high level after centrifugation and the expression of vascular endothelial growth factor (VEGF) and Basic Fibroblast Growth Facto (bFGF) from FDP was observed in vitro. The FDP significantly promoted the wound healing of rats compared with that in control groups. Moreover, the expression of M2 macrophages and VEGF in FDP group were significantly higher than that in the control group. Conclusion: FDP is a kind of stem cell product which can be obtained from adipose tissue by physical centrifugation. The cytotherapeutic effect of FDP makes it a promising product for wound healing in clinics.